Jurisdictional analysis of the land acquisition for the komodo airport expansion - Rudu, Yulianus Efendi; Leki, Maria Serlince Aryuni; Rade, Stefanus Don (Journal of Law Science, 2024)
Airport development often requires land expansion, which implies land acquisition from the community. This process needs to be juridically analyzed to ensure its compliance with applicable laws and regulations, particularly Law No. 5 of 1960 on Agrarian Affairs and Law No. 2 of 2012 on Land Acquisition for Development in the Public Interest. This research aims to examine the process of land acquisition for the expansion of Komodo Airport in terms of juridical aspects, based on the Basic Agrarian Law and Law No. 12 of 2012 concerning Land Acquisition for Development in the Public Interest. The research method used is normative juridical, by examining and analyzing relevant laws and regulations, as well as studying related literature. The results of the research show that airport expansion land acquisition can be carried out subject to the provisions in the Basic Agrarian Law and Law No. 12 of 2012 concerning Land Acquisition for Development in the Public Interest.